2013
DOI: 10.11114/ijsss.v1i1.36
|View full text |Cite
|
Sign up to set email alerts
|

Support, Depressive Symptoms, and the Stigma towards Seeking Mental Health Help

Abstract: Although many individuals are affected by psychological disorders, few will seek professional help. Cultural perceptions might complicate this, as emotional suppression and shame of mental illness predominate in some cultures. This online study investigated factors contributing to the stigma of seeking help among Asian (n=81) and Euro-Caucasian (n=472) students. Depressive symptoms mediated relations between social support and self-stigma for seeking help for mental health problems, as well as for academic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Steptoe [14] also revealed that around 38% of students in Asian regions (e.g., Japan, Korea, and Taiwan) showed depressive symptoms, while less than 20% of students in northwestern Europe and the United States showed depressive symptoms. Similar findings have been found in other cross-cultural studies [15,16] and meta-analysis studies [2]. This difference may be attributable to psychosocial factors such as higher levels of parental expectations and academic pressure [17] but lower social support from parents and friends [16] in adolescents in Asian countries than in Western countries.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Steptoe [14] also revealed that around 38% of students in Asian regions (e.g., Japan, Korea, and Taiwan) showed depressive symptoms, while less than 20% of students in northwestern Europe and the United States showed depressive symptoms. Similar findings have been found in other cross-cultural studies [15,16] and meta-analysis studies [2]. This difference may be attributable to psychosocial factors such as higher levels of parental expectations and academic pressure [17] but lower social support from parents and friends [16] in adolescents in Asian countries than in Western countries.…”
Section: Introductionsupporting
confidence: 85%
“…Similar findings have been found in other cross-cultural studies [15,16] and meta-analysis studies [2]. This difference may be attributable to psychosocial factors such as higher levels of parental expectations and academic pressure [17] but lower social support from parents and friends [16] in adolescents in Asian countries than in Western countries. Besides, as Asian children are usually socialized to show higher levels of self-control, obedience, and respect for authority, as well as avoiding creating burdens for other people, they are less likely to seek family and social support when encountering emotional distress [18].…”
Section: Introductionsupporting
confidence: 85%
“…Stigma is a key contributing factor in whether Asian Americans seek mental health care. Stigma-related barriers, such as "Concerned neighbors or community would have a negative opinion" and "Didn't want others to find out about needed treatment," were measured; they were not endorsed significantly more by Asians with perceived need for mental health treatment than by whites with perceived need, despite prior studies suggesting that stigma plays a large role in unmet need for Asians (4,(37)(38)(39)(40)(41). This finding could represent a shift in how mental health treatment is perceived in the Asian-American community, or it could be due to a lack of nuance in the questions within the survey that were meant to capture stigma.…”
Section: Discussionmentioning
confidence: 97%
“…Another notable barrier to seeking mental health aid is stigma [ 17 - 19 ], which may be perpetuated or endorsed by others or internalized by the individual [ 20 ]. Stigma associated with mental illness precludes many people from seeking face-to-face counseling [ 20 , 21 ], particularly for those experiencing depressive symptoms, stress, and anxiety [ 22 , 23 ]. Results from a study on help-seeking behaviors and access to health care within a university population showed that 20% of students who did not use support services despite reporting symptoms of anxiety and depressive disorders did so because they were worried about what people would think.…”
Section: Introductionmentioning
confidence: 99%